2023
DOI: 10.1186/s12916-023-02757-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations of reproductive factors with incidence of myocardial infarction and ischemic stroke in postmenopausal women: a cohort study

Abstract: Background To assess the association between the reproductive factors of age at menarche, age at menopause, and reproductive span and the incidence of myocardial infarction (MI) and ischemic stroke (IS). Methods We used a population-based retrospective cohort study from the National Health Insurance Service database of Korea including a total of 1,224,547 postmenopausal women. Associations between age at menarche (≤ 12, 13–14 [reference], 15, 16, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 49 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…Some studies have suggested that early menarche is associated with an increased risk of CVDs in women (15)(16)(17). However, a study from Korea determined that late menarche was associated with an increased risk of MI, but early age at menarche was not (13). Another study of 1,088,992 premenopausal women found that late menarche was associated with an increased risk of all-cause disease, while early menarche was not(18).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that early menarche is associated with an increased risk of CVDs in women (15)(16)(17). However, a study from Korea determined that late menarche was associated with an increased risk of MI, but early age at menarche was not (13). Another study of 1,088,992 premenopausal women found that late menarche was associated with an increased risk of all-cause disease, while early menarche was not(18).…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows the summary estimates from the meta-analysis of the association between age at menopause and ischemic stroke. Of these 10 studies, 5 studies defined menopausal age before 45 years old as early menopause [16][17][18][19][20] , The other 5 studies defined menopausal age before 49, 47, 43, 42, and 40 years old as early menopause, respectively [21][22][23][24][25] (Table1). For the age at menopause and the incidence of ischemic stroke, Table2B,2C,2D demonstrate the risk of menopause and ischemic stroke for women whose age at menopause was before 45, 49 and 43 years, respectively.…”
Section: Age At Menopause and Risk Of Ischemic Strokementioning
confidence: 99%
“…Inherited genetic variants may also affect lipid metabolism and cholesterol levels, influencing plaque accumulation and atherosclerosis development, a major cause of MI. Epigenetic processes also mediate estrogen's effects, with studies showing that estrogen utilization and cognitive functions like memory enhancement are dependent on epigenetic mechanisms [27].…”
Section: Modifying Factors and Interactionsmentioning
confidence: 99%